The Effect of Fatigue on the Time to Stability in Jumping and Landing in Football Players Who Have Undergone Anterior Cruciate Ligament Reconstruction - Moosareza Ghorbani; Amir Shamloo Kazemi; Farideh Babakhani (Shiraz University of Medical Sciences, 2022)
Background: Jumping and landing are common activities in soccer that are often reported in connection with anterior cruciate ligament injury. As most injuries occur during fatigue, the present study aimed to investigate the effect of fatigue on the component of time to stability (TTS) during landing between healthy soccer players and soccer players who have undergone anterior cruciate ligament reconstruction.Methods: This quasi-experimental study included 24 professional soccer players who were divided into control and experimental groups. Twelve active professional soccer players (control group) and 12 soccer players with 6-24 months of anterior cruciate ligament reconstruction with hamstring graft (experimental group) participated in this study. Athletes jumped and landed on the obstacle to a height of 7.5 cm. After the fatigue protocol, these movements were repeated. TTS data was collected using force plate. MANOVA test at the significant level of p <0.05 was used to compare pre-test and post-test data between the groups.Results: According to the results of this study, fatigue did not affect the time to stability in any of the anterior-posterior (p=0.104), internal-external (p=0.668), or vertical components (p=0.894) between the two groups, and fatigue could not make a significant difference between the two groups. Moreover, before fatigue, no significant difference was observed between the two groups in any of the components.Conclusion: It seems that a plyometric fatigue training session will not be effective in differentiating between healthy soccer players and soccer players who have had anterior cruciate ligament reconstruction.